The predictive value of histometry of thyroid tissue in anticipating hypothyroidism after subtoatl thyroidectomy for primary thyrotoxicosis. - Young, R J (1975)
Thyroid tissue removed at partial thyroidectomy from primary thyrotoxicosis patients, after preparation for operation with carbimazole and Lugol's iodine, was studied with the histometric technique. In patients with little or no evidence of autoimmunity before operation, the chance of developing postoperative hypothyroidism was approximately 1 in 2 in those who had volume percentage of epithelium greater than 40, but only approximately 1 in 10 in those who had volume percentage of epithelium less than 40. This approach may ultimately prove of predictive value in a substantial proportion of patients for anticipating hypothyroidism after subtotal thyroidectomy for primary thyrotoxicosis.